2020
DOI: 10.1039/d0nj04187d
|View full text |Cite
|
Sign up to set email alerts
|

Boronic acids for functionalisation of commercial multi-layer graphitic material as an alternative to diazonium salts

Abstract: A novel radical-based functionalisation strategy for the synthesis of functionalised commercially obtained plasma-synthesised multi-layer graphitic material (MLG) is presented herein. 4-(trifluoromethyl)phenyl boronic acid was utilised as a source of 4-(trifluoromethyl)phenyl...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 56 publications
2
6
0
Order By: Relevance
“…74-1739), respectively. 42,43 There are some modifications on the diffractograms of the obtained 2D nanomaterials compared with those of Fig S2b (ESI †), primarily because of the smaller size of the 2D Ag 2 SO 4 compared to the bulk crystal, which is in excellent agreement with previous reports. 44,45 In addition, preferential growth of the crystal planes during the synthesis may affect the final dominant crystal planes in which the number of net planes (222) in the obtained 2D Ag 2 SO 4 nanosheets is greater than all other net planes.…”
Section: Resultssupporting
confidence: 89%
“…74-1739), respectively. 42,43 There are some modifications on the diffractograms of the obtained 2D nanomaterials compared with those of Fig S2b (ESI †), primarily because of the smaller size of the 2D Ag 2 SO 4 compared to the bulk crystal, which is in excellent agreement with previous reports. 44,45 In addition, preferential growth of the crystal planes during the synthesis may affect the final dominant crystal planes in which the number of net planes (222) in the obtained 2D Ag 2 SO 4 nanosheets is greater than all other net planes.…”
Section: Resultssupporting
confidence: 89%
“…The first stage of our investigation involved the preparation of a MLG composite (MLG-PP) consisting of MLG, PDDA and PFO which displayed oleophobic properties. The MLG material used for this was synthesised via a plasma exfoliation process providing multi-layered stacks of graphitic material (see experimental section and reference 6 for further details). The synthesis of the composite was achieved via a two-step process comprised of initial adsorption of PDDA onto MLG.…”
Section: Synthesis and Analysis Of Mlg-pp Composite Filmsmentioning
confidence: 99%
“…The development of materials which possess oil/water separation capabilities represents an area of intense interest. [1][2][3][4][5] As part of our ongoing investigations 6,7 focusing on commercially obtained plasma-synthesised multi-layer graphitic material (MLG), 8 we became interested in utilising MLG as a scaffold for the development of composite materials. Similar materials based on graphene oxide and SiO2 nanoparticles have previously found promise within this application.…”
Section: Introductionmentioning
confidence: 99%
“…Herein, we report a detailed analysis of a plasma-exfoliated material. Whilst our previous work reveals the presence of large slit pores within similar plasma-exfoliated graphitic material via BJH analysis, 22 we now demonstrate the application of BJH data to provide actual estimations of the distance between these stacks. It was found that such materials possess large separations between subsequent stacks, thus providing desirable properties including enhanced friability and ease of entry for intercalation compounds.…”
Section: Introductionmentioning
confidence: 64%
“…21 As shown within our previous work, such materials exhibit large slit pores between orderly defined stacks of layers, as indicated through Barret-Joyner-Halenda (BJH) analysis. 22 Within the context of pore analysis during adsorption/desorption experiments, the gaseous adsorbate of choice is very important. The kinetic diameter and shape of the adsorbate govern its ability to penetrate a pore.…”
Section: Introductionmentioning
confidence: 99%